The Validation and Modification of the Caprini Risk Assessment Model for Evaluating Venous Thromboembolism after Joint Arthroplasty - Qiao, Liang; Yao, Yao; Wu, Dengxian; Xu, Ruijuan; Cai, Honggang; Shen, Ying; Xu, Zhihong; Jiang, Qing (Thrombosis and Haemostasis, 2023)
Background The Caprini risk assessment model (RAM) is the most commonly used tool for evaluating venous thromboembolism (VTE) risk, a high score for arthroplasty can result in patients being classified as high risk for VTE. Therefore, its value in post-arthroplasty has been subject to debate.Methods Retrospective data were collected from patients who underwent arthroplasty between August 2015 and December 2021. The study cohort included 3,807 patients, all of whom underwent a thorough evaluation using Caprini RAM and vascular Doppler ultrasonography preoperatively.Results A total of 432 individuals (11.35%) developed VTE, while 3,375 did not. Furthermore, 32 (0.84%) presented with symptomatic VTE, while 400 (10.51%) were detected as asymptomatic. Additionally, 368 (9.67%) VTE events occurred during the hospitalization period, and 64 (1.68%) cases were detected during postdischarge follow-up. Statistical analysis revealed significant differences between the VTE and non-VTE groups in terms of ages, blood loss, D-dimer, body mass index >25, visible varicose veins, swollen legs, smoking, history of blood clots, broken hip, percent of female, hypertension, and knee joint arthroplasty (p < 0.05). The Caprini score was found to be significantly higher in the VTE group (10.10 ± 2.23) compared with the non-VTE group (9.35 ± 2.14) (p < 0.001). Furthermore, there was a significant correlation between the incidence of VTE and the Caprini score (r = 0.775, p = 0.003). Patients with a score ≥9 are at a high-risk threshold for postoperative VTE.Conclusion The Caprini RAM shows a significant correlation with the occurrence of VTE. A higher score indicates a greater likelihood of developing VTE. The score ≥9 is at particularly high risk of developing VTE.
Keywords: Caprini risk assessment model (RAM); venous thromboembolism (VTE); arthroplasty